2017
DOI: 10.1177/0885066617732747
|View full text |Cite
|
Sign up to set email alerts
|

High Early Fluid Input After Aneurysmal Subarachnoid Hemorrhage: Combined Report of Association With Delayed Cerebral Ischemia and Feasibility of Cardiac Output–Guided Fluid Restriction

Abstract: High early fluid input was associated with DCI. Invasive hemodynamic monitoring was feasible to reduce fluid input while maintaining preload. These results indicate that fluid loading beyond a normal preload occurs, may increase DCI risk, and can be minimized with TPT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…The findings of this study provide support and confirm those of previous studies, 2,4 and pave the way for further, preferably multicenter, investigations on early hemodynamic and fluid management as an essential part of critical care management of aneurysmal subarachnoid hemorrhage.…”
Section: To the Editorsupporting
confidence: 88%
“…The findings of this study provide support and confirm those of previous studies, 2,4 and pave the way for further, preferably multicenter, investigations on early hemodynamic and fluid management as an essential part of critical care management of aneurysmal subarachnoid hemorrhage.…”
Section: To the Editorsupporting
confidence: 88%
“…Higher fluid intake in aSAH has been associated with significant complications, such as pulmonary edema, prolonged intubation, DCI, and poor functional outcomes. 225,226 The HIMA-LAIA trial was the first RCT investigating the role of induced hypertension in DCI. The trial did not demonstrate any benefit in the induced hypertension group with a risk ratio for serious adverse events of 2.1 (95% CI, 0.9 to 5.0), although the trial was ended early because of negative results and slow recruitment.…”
Section: Diagnosismentioning
confidence: 99%
“…For example, euvolemia is currently recommended in patients with brain injury, given increasing evidence found that both hypovolemia and hypervolemia are associated with unfavourable outcomes [ 30 ]. Vergouw et al investigated 246 patients with aneurysmal subarachnoid haemorrhage and reported that an increased early day 1–3 fluid input was associated with the incidence of delayed cerebral ischemia [ 31 ]. Similarly, Rass et al recently reported that a higher day 1–2 fluid input, instead of day 1–2 fluid balance, was associated with the outcome, including prolonged mechanical ventilation, early brain oedema, anaemia, delayed cerebral ischemia and 3-month functional status, in 237 patients with non-traumatic subarachnoid haemorrhage enrolled between 2010 and 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in line with our data, Rass et al illustrated daily fluid balance from day-1 to day-15 after the incident of subarachnoid haemorrhage and explicitly demonstrated that fluid balance generally reaches a stable status on approximately day-6/day-7 after the subarachnoid haemorrhage, suggesting the crucial role of fluid balance in critically ill neurological patients [ 32 ]. Unlike increasing studies that have shown a slightly increased comorbidity and mortality rate among critically ill neurological patients with a positive fluid balance in days 1–3, evidence of the impact of fluid balance beyond day-3 is sparse [ 31 , 33 ]. Hence, the data in the present study provide crucial evidence regarding the long-term mortality impact of day 4–7 fluid balance in critically ill surgical patients.…”
Section: Discussionmentioning
confidence: 99%